Endocystectomy as a conservative surgical treatment for hepatic cystic echinococcosis: a systematic review with single-arm meta-analysis - Saeedi, Mohammed al; Ramouz, Ali; Khajeh, Elias; El Rafidi, Ahmad; Ghamarnejad, Omid; Shafiei, Saeed; Ali-Hasan-Al-Saegh, Sadeq; Probst, Pascal; Stojković, Marija; Weber, Tim; Hoffmann, Katrin; Mehrabi, Arianeb (PLoS neglected tropical diseases, 2021)
Background In patients with hepatic cystic echinococcosis (CE), treatment effectiveness, outcomes, complications, and recurrence rate are controversial. Endocystectomy is a conservative surgical approach that adequately removes cyst contents without loss of parenchyma. This conservative procedure has been modified in several ways to prevent complications and to improve surgical outcomes. This systematic review aimed to evaluate the intraoperative and postoperative complications of endocysectomy for hepatic CE as well as the hepatic CE recurrence rate following endocystectomy. Methods A systematic search was made for all studies reporting endocystectomy to manage hepatic CE in PubMed, Web of Science, and Cochrane CENTRAL databases. Study quality was assessed using the methodological index for non-randomized studies (MINORS) criteria and the Cochrane revised tool to assess risk of bias in randomized trials (RoB2). The random-effects model was used for meta-analysis and the arscine-transformed proportions were used to determine complication-, mortality-, and recurrence rates. This study is registered with PROSPERO (number CRD42020181732). Results Of 3,930 retrieved articles, 54 studies reporting on 4,058 patients were included. Among studies reporting preoperative anthelmintic treatment (31 studies), albendazole was administered in all of them. Complications were reported in 19.4% (95% CI: 15.9-23.2; I2 = 84%; p-value <0.001) of the patients; biliary leakage (10.1%; 95% CI: 7.5-13.1; I2 = 81%; p-value <0.001) and wound infection (6.6%; 95% CI: 4.6-9; I2 = 27%; p-value = 0.17) were the most common complications. The post-endocystectomy mortality rate was 1.2% (95% CI: 0.8-1.8; I2 = 21%; p-value = 0.15) and the recurrence rate was 4.8% (95% CI: 3.1-6.8; I2 = 87%; p-value <0.001). Thirty-nine studies (88.7%) had a mean follow-up of more than one year after endocystectomy, and only 14 studies (31.8%) had a follow-up of more than five years. Conclusion Endocystectomy is a conservative and feasible surgical approach. Despite previous disencouraging experiences, our results suggest that endocystectomy is associated with low mortality and recurrence.
Gesehen am 27.06.2022